Multi-mycotoxin occurrence and their risk to poultry health in semi-intensive broiler farms in Kenya - Njaramba, Jane K.; Muloi, Dishon M.; Velde, M.V.; Saeger, S.D.; Ibayi, Eugine L.; Moodley, Arshnee; Antonissen, G. (Elsevier, 2025)
Scarcity of feed ingredients, unregulated feed mills, and limited monitoring of mycotoxin levels in feed increase the risk of mycotoxin exposure for poultry in sub-Saharan Africa. This study examined mycotoxins in feed from 122 Kenyan broiler farms and an association between on-farm feed handling practices and mycotoxin levels. Using a validated multi-mycotoxin liquid chromatography-tandem mass spectrometry method (LC-MS/MS), all feed samples contained at least one mycotoxin and 93% (n=113) had >3 mycotoxins. The most prevalent EU-regulated mycotoxins detected were fumonisins (92.6%; 72.7 – 1285.3 μg/kg), deoxynivalenol (88%; 96.6 – 2131.2 μg/kg), aflatoxins (37%; 4.2 – 87.8 μg/kg), and ochratoxin A (4%; range 14.90 – 59.20 μg/kg). Deoxynivalenol, fumonisins, and zearalenone frequently co-occurred in the feed samples. Among the surveyed farms, 33% (n= 40) were at risk of subclinical exposure to deoxynivalenol, while 14% and 7% faced similar risks from total aflatoxins and fumonisins, respectively. Univariate analysis found no significant associations between farm-specific feed handling practices and mycotoxin levels in feed. This study found a high co-occurrence of mycotoxin at low to moderate concentrations in compound broiler feed from the selected farms. While these levels pose a potential risk, no direct link to broiler health outcomes was found. Our findings highlight the need for further research to explore the effects of subclinical mycotoxin exposure on broilers and to develop context-specific mycotoxin level guidelines for the region.